To seal or to vent? Hemodynamic-guided decision-making in an older patient with borderline large secundum atrial septal defect and pulmonary hypertension - Tambunan, Daniel; Valerinna Yogibuana (Heart Science Journal, 2026)
Background: Determining whether an atrial septal defect (ASD) should be closed in older patients who already have pulmonary hypertension may present a clinical dilemma. This is particularly true when pulmonary vascular resistance (PVR) approaches commonly used operability thresholds. Case Illustrations: A 59-year-old woman was referred to our center because of progressive exertional dyspnea and declining functional capacity. Echocardiography evaluation showed a large secundum ASD with a significant left-to-right shunt and right-sided chamber enlargement. Right heart catheterization revealed a mean pulmonary artery pressure of 46 mmHg and a pulmonary vascular resistance of 7.1 Wood units. Following oxygen test, PVR decreased to 3.4 Wood units and the Qp/Qs ratio increased from 1.5 to 2.65, suggesting preserved pulmonary vascular responsiveness. Based on these findings,  transcatheter ASD closure without fenestration was performed successfully. The intervention was completed without complications, and early follow-up showed improvement in symptoms along with more favorable hemodynamic findings. Conclusions: This case highlights how comprehensive hemodynamic and physiological assessment, including dynamic vasoreactivity testing, can guide operability decisions in older patients with ASD and elevated PVR. Reassessment of pulmonary vascular responsiveness may refine risk stratification and support individualized management.